Teacher-Researcher: Uncertainties of Knowledge - Mosquera-Albornoz, Deivis Robinson; Supple, Sebastián Nathanial; Quiceno, Guillermo Rojas; López-Zuluaga, José Miguel (Information Research Communications, 2024)
Introduction This study examines the scientific production related to the role of the teacher-researcher over the past years. The objective is to analyze the evolution of publications in this field, identifying key trends and collaboration patterns among researchers. Understanding these aspects is essential to recognize the development of knowledge in this area and its impact on academic communities. Methods A bibliometric approach was used, selecting articles from indexed databases published over the last 24 years. A network analysis methodology was applied to identify the most influential works and the connections among researchers. The classification of references was conducted based on their contribution to the academic discussion, differentiating between foundational works and recent developments. Data visualization techniques were employed to illustrate the main research lines and collaborative networks. Results The findings indicate a steady increase in the number of publications, with a significant rise in recent years. Recurring thematic patterns were identified, as well as a growing network of collaboration among researchers from different institutions. The classification of references highlights well-established research areas, while others present opportunities for further exploration. Conclusions This study provides a comprehensive view of the evolution of research on the teacher-researcher role, emphasizing its relevance within the academic community. Encouraging interdisciplinary collaboration and open access initiatives could enhance the impact and development of research in this field.
Keywords: Teacher research; Hidden science and learning; Uncertainty in education; Research-teaching nexus; Scientometric mapping